O impacto das casas-abrigo no rompimento do ciclo de violência contra mulher cometida por parceiro íntimo - Rodrigues, Júlia Bianchini (Universidade Federal de São Carlos, 2024)
The present study theoretically explores the impact of shelters on breaking the cycle of violence against women, particularly those committed by intimate partners. Based on a review of recent literature, the study investigated how these institutions function as essential factors of protection and support. The aim was to understand how shelters contribute to interrupting the cycle of violence by providing a safe environment and empowerment programs that aid in the recovery and reintegration of victims. The findings indicate that, in addition to offering physical protection, these institutions promote the emotional and social empowerment of women, although they still face challenges related to social reintegration and the need for public policies adapted to local realities. It was concluded that, despite these challenges, shelters play a crucial role in protecting women and preventing femicides, requiring continuous support to maximize their effectiveness.
The impact of shelter houses in breaking the cycle of violence against women commited by an intimate partner
Keywords: Violência contra a mulher; Casa abrigo; Ciclo da violência; Domestic violence; Shelters; Violence cycle; CIENCIAS HUMANAS::PSICOLOGIA::TRATAMENTO E PREVENCAO PSICOLOGICA